Sex And Money : Feminism and Political Economy in the Media - Riordan, Ellen; Meehan, Eileen R., 1951- (Book collections on Project MUSE., 2002)
"This groundbreaking volume uses the media to show how questions of gender and economics are inextricably linked to issues of power in Western capitalist societies. Integrating political economy and feminism, it offers a new understanding of communication at the personal, experiential, institutional, and structural levels--and exposes all the subtle and complex ways in which sex and money are sutured into individuals' daily lives."--Provided by publisher.